Illicit markets, violence, warlords, and governance: West African cases - Reno, William (Crime, law and social change, 2009)
It is commonly assumed that wartime leaders of illicit commercial networks engage in exploitative behavior and lack popular support. Evidence from West Africa suggests otherwise. Some wartime leaders use their commercial activities in post-conflict situations to build political support among demobilized fighters. Wartime leaders may then use these relationships to launch successful electoral campaigns and to protect themselves from political marginalization or even prosecution for their wartime activities. These developments represent the emergence of new forms of governance outside the framework of imported notions of reform and state-building.